(untitled) (Research, Society and Development, 2020)
The objective of the work was to analyze the impact of social isolation on people’s lives during the Covid-19 pandemic period. 73, over 18 years old participated in the research; 68.5% were female and 31.5% were male. The research was applied individually online. For data analysis, the software IRAMUTEQ (Interface of Repourles Analyzes Multidimensionnelles de Texteset de Questionnaires version 0.7) and the software IBM SPSS for Windows (version 25) were used. To analyze the open question present in the questionnaire, it was carried out through the Discourse Analysis proposed by Laurence Bardin. In this way, it was possible to realize that this moment in history is proving to be very challenging for the subjects that generate great impact on physical and mental health, as it is a moment where people had to distance themselves from their cycles, generating fear, loneliness, uncertainty and even psychological problems like anxiety, stress and depression.